The benefits of neutrality: Saudi foreign policy in the wake of the Ukraine war - Jens Heibach (Global Policy, 2024)
This article assesses Saudi Arabia's ambivalent response to Russia's invasion of Ukraine in February 2022. On the one hand, the Kingdom has publicly condemned Russia's military aggression as contravening international law. Yet, on the other, it has also failed to take serious measures against Moscow, notably by refusing to join in Western attempts to prevent Russia from earning hydrocarbon revenues on the international market. Saudi Arabia has adopted a neutral position instead, offering to mediate between the warring parties while simultaneously repeatedly rebuffing its longtime ally the United States. By reviewing the Kingdom's foreign policy moves and narratives since the war's onset, it is argued Saudi officials are acting perfectly rationally in that they strive to achieve the optimum outcome as per their definition of Saudi national interests in this conflict, thereby pressing ahead with the diversification of Saudi foreign policy initiated roughly one decade earlier. In concluding, the implications of the Kingdom's stance on the war for future global order-making are discussed.
Keywords: 320